Norwegian Broadside Ballads and the Collecting Practices of Thorvald Boeck - Cowan, Yuri (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
In nineteenth‑century Norway there were, as there had been in Britain, a few forward‑thinking collectors who even in the earliest days of the formation of the modern Norwegian nation recognized that cheap, ephemeral documents of street literature like broadside ballads would someday be worth preserving, as significant witnesses to the printing history, local history, everyday reading, and popular culture of their time. One of the largest such collections of so‑called “skillingsviser” formed part of the library of the jurist Thorvald Boeck (1835‑1901), whose large and inclusive collection of Norwegian belles lettres and general literature remained intact after his death and is now an important part of the Gunnerus rare book library in Trondheim.The ballads represented a kind of history from below, since their annotations on these ballads preserve personages and small incidents from local history that might otherwise have been forgotten. They also represented a kind of print culture that was at once ubiquitous and, because disposable, in danger of being lost. And yet it took a certain kind of foresight to recognize the value of these printed objects, and to preserve them. Drawing on comparative study with Norwegian, Danish, and English collectors; on the memoirs of bookdealers and literary writers of the time; and on the still more material witness of provenance notes, marginalia, and bookplates on the extant ballads themselves, this article works to characterize the motives and collecting practices that led to the ballads’ inclusion in Boeck’s great private library.